Nanogel receptors for high isoelectric point protein detection: influence of electrostatic and covalent polymer–protein interactions. Issue 45 (4th May 2020) - Wechsler, Marissa E.; Dang, H. K. H. Jocelyn; Dahlhauser, Samuel D.; Simmonds, Susana P.; Reuther, James F.; Wyse, Jordyn M.; VandeWalle, Abigail N.; Anslyn, Eric V.; Peppas, Nicholas A.
Abstract : Synthesis of an aldehyde acrylate-based functional monomer and incorporation into poly( N -isopropylacrylamide- co -methacrylic acid) nanogels for use as high pI protein receptors. Abstract : An aldehyde acrylate-based functional monomer was incorporated into poly( N -isopropylacrylamide- co -methacrylic acid) nanogels for use as protein receptors. The aldehyde component forms dynamic imines with surface exposed lysine residues, while carboxylic acid/carboxylate moieties form electrostatic interactions with high isoelectric point proteins. Together, these interactions effect protein adsorption and recognition.